Inflation and growth: A new Keynesian perspective - Robert Amano; Tom Carter; Kevin Moran (Bank of Canada, 2012)
The long-run relation between growth and inflation has not yet been studied in the context of nominal price and wage rigidities, despite the fact that these rigidities now figure prominently in workhorse macroeconomic models. We therefore integrate staggered price- and wage-setting into an endogenous growth framework. In this setting, growth and inflation are linked via the incentive to innovate. For standard calibrations, the linkage is strong: as trend inflation shifts from -5 to 5 percent, the range over which the economy's steady-state growth rate varies spans 50 basis points, implying up to a 15 percent output differential after thirty years. Nominal wage rigidity plays a critical role in generating these results, and compounding of inflation's growth effects implies large welfare losses. Endogenous growth thus proves a key channel via which inflation impacts New Keynesian economies.
Keywords: E31; E52; O31; O42; 330; Inflation: costs and benefits